Physical activity and functional abilities in adult males with haemophilia: a cross‐sectional survey from a single US haemophilia treatment centre. (10th April 2013) - Baumgardner, J.; Elon, L.; Antun, A.; Stein, S.; Ribeiro, M.; Slovensky, L.; Kempton, C.L.
Summary Physical activity and functional ability are important determinants of quality of life and these metrics are affected by both haemophilia and ageing. Outside haemophilic arthropathy, risk factors leading to reduced physical activity and function in people with haemophilia (PWH) are under‐explored. The purpose of this analysis was to determine risk factors for reduced physical activity and functional limitations in PWH. A secondary analysis was conducted on data indexing physical activity and functioning of 88 PWH using data originally collected as part of a cross‐sectional study at a single large haemophilia treatment centre. The Framingham Physical Activities Index (PAI), the Hemophilia Activities List (HAL) and the Timed Up‐and‐Go Test (TUG) were the outcome measures. The World Federation of Haemophilia (WFH) orthopaedic joint score was used as a measure of arthropathy. Multiple linear regression analysis was used to assess the relationship between the outcome measures and covariates. Worsening WFH joint score was independently associated with all three outcome measures (P < 0.05). Increasing age was associated with reduced PAI and increased TUG time (P < 0.05). The HAL summary score was decreased in patients with chronic liver disease (P = 0.006). The adjusted R2 for each model was ≤0.35. This study provides evidence for the relationship between arthropathy and reduced physical functioning/activity, but also highlights that much of the variation in physical functioning/activity is not explained by haemophilia‐related characteristics.